Pengaruh Motivasi Terhadap Minat Berwirausaha Melalui Efikasi Diri Pada Mahasiswa Fakultas Syariah Dan Dakwah IAIN Sorong Angkatan 2022 - Siti Fatimah Azzahra; Rokhimah; Istika Ahdiyanti (Institut Agama Islam Negeri Kendari, 2026)
This study examines the role of self-efficacy as a mediating variable between motivation and entrepreneurial intention among students of the Faculty of Sharia and Da'wah at IAIN Sorong, class of 2022. A quantitative approach was employed, with data analysed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS software. The entire active student population of the faculty (n = 74) served as the sample through a saturated sampling technique. The findings reveal that: (1) motivation exerts a positive and significant effect on entrepreneurial intention (β = 0.441; p = 0.000); (2) motivation positively and significantly influences self-efficacy (β = 0.722; p = 0.000); (3) self-efficacy positively and significantly affects entrepreneurial intention (β = 0.375; p = 0.001); and (4) self-efficacy partially mediates the relationship between motivation and entrepreneurial intention (indirect effect = 0.319). The model demonstrates strong explanatory power (R² entrepreneurial intention = 0.574; R² self-efficacy = 0.522) and satisfies all model fit criteria (SRMR = 0.083 < 0.10). These findings underscore the importance of institutional programmes that simultaneously nurture student motivation and strengthen self-efficacy within an entrepreneurial development context.